Analysing material well-being: the role of socio-demographic and socio-economic factors / Nurul Amyra Mat Isa and Siti Nurul Akma Ahmad - Mat Isa, Nurul Amyra; Ahmad, Siti Nurul Akma (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Well-being is comprised of material well-being (such as income, jobs, and housing) but also the broader quality of people's lives, including healthcare, education, environment, and social connections. However, based on the OECD Malaysia Economic Survey 2019 shows that there is slow progress in areas of health and family weighed on the improvement of well-being. Thus, the aim of this study is to identify the influence of socio-demographic and socio-economic with material well-being in society. The survey was conducted in Alor Gajah, Melaka, which involves society as a study population with 160 useable respondents. Our findings revealed that there is a significant influence between socio-economic and material well-being. Thus, Malaysia and other developing countries should focus on enhancing the well-being of the population by conducting robust research on well-being.